(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2025)
Sea level is rising and it is expected to continue rising as the atmosphere is warming inducing glacier melting. Based on this melting a minimum of 0.4 m of sea level rise (SLR) is expected for the year 2100. Coastal erosion is the more evident consequence of this SLR. At estuarine areas these effects are more difficult to discern. In some areas climate is warming and rains are increasing, and are thought to continue doing so in Buenos Aires; but they are decreasing in Patagonia. Therefore, estuarine areas, freshwater and salt marshes have different responses along the Argentine coast. More important are the effects in urban areas where planners and administrators have systematically disregarded the subject. In low-lying areas as Samborombón Bay the SLR will cause a surface retreat of the salt-fresh water interactions. Therefore, General Lavalle city will be more dependant of the surface freshwater runoff of the Channel 2. Flash floods today can affect the city of San Clemente del Tuyú but the performance of the discharge pipelines depends on the meteorological effects on the tides. Flash floods have also affected coastal cities of the desertic Patagonia: Puerto Madryn and Comodoro Rivadavia have suffered unprecedented floods during recent years. Two models applied to coast evolution in response to SLR. Bruun`s model predicts shore erosion and deposition below the depth where there is no wave action (closure depth). However, in low-lying areas where there is enough sediment availability the onshore migration of bedforms (beaches, cheniers) can occur. Changes in estuarine areas are more difficult to predict. Tidal prisms can increase significantly in microtidal coasts due to SLR, but in macrotidal coasts these increments were not significant. Another effect of the SLR occurs at the hydrogeological interphase between fresh and salt waters. The simulation of these interactions should be carefully estimated considering the groundwater discharge and the climate change effects on the Precipitation.